Integrated Farming System: A boon in hill farming system - Roy, Rakesh; Kharga, Basu Deo (Indian Farming, 2022)
Sustainable income and consistent employment can be achieved by the farming community by adopting IFS. The economic analysis of different components under IFS in hill farming system has shown considerably superior benefit : cost ratio. Economics of the IFS clearly shows that return was higher in livestock units in comparison to horticultural or agricultural crop. The IFS under study also demonstrated that it had created annual mandays of more than 1685 days.